Особливості структури сумішей карбоксиметилцелюлози та карбоніл- або гідроксилвмісного полімеру - Штомпель, В.І.; Овсянкіна, В.О.; Керча, Ю.Ю. (Видавничий дім "Академперіодика" НАН України, 2007)
By using methods of x-ray structural analysis, we have established that there is a small amount of intermolecular hydrogen bonds between polar groups of carboxymethylcellulose and polyvinylpyrrolidone. As a result, the structure of these blends is homogeneous. This is a consequence of the noncompatibility of the blend components. The intensity of intermolecular hydrogen bonds is increased in the blends of carboxymethylcellulose and poly(vinyl alcohol) that leads to the appearance of the microheterogeneous structure of blends which are enriched by poly(vinyl alcohol). It's the sign of a partial compatibility of components of this compound.